Standards of practice in acute ischemic stroke intervention international recommendations - Pierot, Laurent; Hacke, Werner; Brugge, Karel G. ter (The journal, 2019)
After five positive randomized controlled trials showed benefit of mechanical thrombectomy in the management of acute ischemic stroke with emergent large-vessel occlusion, a multi-society meeting was organized during the 17th Congress of the World Federation of Interventional and Therapeutic Neuroradiology in October 2017 in Budapest, Hungary. This multi-society meeting was dedicated to establish standards of practice in acute ischemic stroke intervention aiming for a consensus on the minimum requirements for centers providing such treatment. In an ideal situation, all patients would be treated at a center offering a full spectrum of neuroendovascular care (a level 1 center). However, for geographical reasons, some patients are unable to reach such a center in a reasonable period of time. With this in mind, the group paid special attention to define recommendations on the prerequisites of organizing stroke centers providing medical thrombectomy for acute ischemic stroke, but not for other neurovascular diseases (level 2 centers). Finally, some centers will have a stroke unit and offer intravenous thrombolysis, but not any endovascular stroke therapy (level 3 centers). Together, these level 1, 2, and 3 centers form a complete stroke system of care. The multi-society group provides recommendations and a framework for the development of medical thrombectomy services worldwide.